(untitled) (Biological Sciences - PJSIR, 2006)
. Investigations have been carried out on the development of stabilized crude animal amylases for enzymatic desizing of woven fabric. Animal amylases from pancreas were extracted and stabilized for industrial use. The ex- tracted pancreatic amylases took 1 h in exhaust process and 6 h in pad batch process for the desizing of woven fabric. The desizing performance of these amylases was also compared with commercially available enzymes. The present studies have yielded highly active and stabilized amylases from animal pancreas. The method used for the enzyme recovery was also noted to give good yield of the enzyme from animal origin.